Psychological approach to the activity of man - Radžvilas, V. (Psichologija, 1982)
The term "activity" is often used to characterize various psychic processes and still needs closer definition. This problem may be formulated as the problem of determinism of psychic development of man. A psychoanalytical theory of S. Freud and behaviourism represent two opposite approaches to its solution in bourgeois psychology. Soviet psychology deals with this problem on the basis of materialistic-dialectical methodology. A structural-functional approach to the development of human psyche developed in works of some prominent Soviet psychologists throws a new light upon the problem of human activity. L. I. Bozhovich, French psychologist A. Wallon and some Soviet and foreign Marxist philosophers consider that man inherits a psychological mechanism which enables him to join any existing social structure.
Keywords: activity; Freud; Wallon; Bozhovich